Constructivist Perspective on Developing a Multidimensional Blended Teaching Model Fostering Deep Learning - Li, Xiumei; Ye, Min; Huang, Chi-Hsuan; Wu, Yu-Ping (International Journal of Humanities and Education Development (IJHED), 2023)
To promote high-quality development of higher education, it is imperative to facilitate students’ transition from surface learning to deep learning. Compared with surface learning that focuses on rote memorization, deep learning emphasizes meaningful learning based on understanding and transfer. It involves three progressively advanced cognitive stages of knowing: "learning for understanding," "learning for application," and "learning for innovation," which ultimately enable the internalization, transfer, and creative application of knowledge. How to foster deep learning in students has been an urgent issue of higher education. This study, grounded in constructivist learning theory, explores a multidimensional blended teaching model fostering deep learning. It also develops an evaluation system assessing learning outcomes from the perspectives of ideological, political and moral education, knowledge, and competencies. We conducted an empirical study to test the effectiveness of this multidimensional blended teaching model. Findings will provide theoretical and practical implications for teaching reforms of similar courses.